Single incision laparoscopic bariatric surgery: challenging the conventional - Reynu Rajan,; Neeraj K,; Kosai NR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Sleeve gastrectomy has gained popularity over the years and is commonly performed laparoscopically through multiple small incisions. The arrival of single incision laparoscopic surgery has been a game changer, allowing for sleeve gastrectomy to be performed through a cosmetically more appeasing scar with improved patient satisfaction. In this article, we describe the history, technical challenges, proposed solutions to some of the hurdles faced during single-incision laparoscopic bariatric surgery and highlight our method of performing single incision laparoscopic sleeve gastrectomy purely through a single access device.